Bioethical study of the behavioral response of birds to noise disturbance from human activities in the coastal area of North Sumatra - Grace Jessica Nadeak; Haziar Anisya Hakim; M Fadil Akbari; Khairiza Lubis; Nurbaity Situmorang (EduMatika: Jurnal MIPA, 2026)
Noise generated by human activity is a form of environmental disturbance that has the potential to affect wildlife behavior, including birds that rely heavily on acoustic communication for their daily activities. This study aims to analyze the influence of human noise on bird activity and behavior in the coastal area of ??Sejarah Beach, Batubara Regency, North Sumatra. This study used a qualitative approach with descriptive methods through direct field observations from January 28 to February 2, 2026. Data were collected through observations of bird activity and human activity around the observation area, such as visitor conversations, footsteps, and other tourist activities that produce sound. The results of the observations indicate that birds engage in various activities, such as foraging, resting, and grooming, when the environment is relatively quiet. However, increased human activity that produces noise causes birds to increase their vigilance and move to quieter areas. This suggests that anthropogenic noise can affect bird behavior patterns and habitat utilization in coastal areas. Therefore, the application of environmental management principles and wildlife observation ethics is necessary to minimize disturbances to natural bird activities and support conservation efforts in coastal areas.